Noncoding regulatory sequences of Ciona exhibit strong correspondence between evolutionary constraint and functional importance - Johnson, David S.; Davidson, Brad; Brown, Christopher D.; Smith, William C.; Sidow, Arend (Genome Research, 2004)
We show that sequence comparisons at different levels of resolution can efficiently guide functional analyses of regulatory regions in the ascidians Ciona savignyi and Ciona intestinalis. Sequence alignments of several tissue-specific genes guided discovery of minimal regulatory regions that are active in whole-embryo reporter assays. Using the Troponin I (TnI) locus as a case study, we show that more refined local sequence analyses can then be used to reveal functional substructure within a regulatory region. A high-resolution saturation mutagenesis in conjunction with comparative sequence analyses defined essential sequence elements within the TnI regulatory region. Finally, we found a significant, quantitative relationship between function and sequence divergence of noncoding functional elements. This work demonstrates the power of comparative sequence analysis between the two Ciona species for guiding gene regulatory experiments.
10.1101/gr.2964504